2018
DOI: 10.4103/jisp.jisp_290_17
|View full text |Cite
|
Sign up to set email alerts
|

Association of pentraxin and high-sensitive C-reactive protein as inflammatory biomarkers in patients with chronic periodontitis and peripheral arterial disease

Abstract: Context:Inflammation is a common feature of both peripheral artery disease (PAD) and periodontal disease.Aim:The aim of this study is to evaluate the relationship between PAD and periodontal disease by examining the levels of inflammatory cytokines, pentraxin-3 (PTX-3), and high-sensitive C-reactive protein from serum.Materials and Methods:A total of 50 patients were included in this cross-sectional study. Patients were divided into two groups: those with PAD (test group) and those with the non-PAD group (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…They did not find any statistically significant association in their regression analysis using the visual analogue scale The interesting result in our study, was the use of HS-CRP for our patients, which allows the detection of minor elevations in CRP. This index has previously been shown was associated with coronary events [21]. Vit D has been rigorously studied regarding its association with pain [22][23][24].…”
Section: Discussionmentioning
confidence: 98%
“…They did not find any statistically significant association in their regression analysis using the visual analogue scale The interesting result in our study, was the use of HS-CRP for our patients, which allows the detection of minor elevations in CRP. This index has previously been shown was associated with coronary events [21]. Vit D has been rigorously studied regarding its association with pain [22][23][24].…”
Section: Discussionmentioning
confidence: 98%
“…The interesting result in our study, was the use of HS-CRP for our patients, which allows the detection of minor elevations in CRP. This index has previously been shown was associated with coronary events [ 21 ]. Vit D has been rigorously studied regarding its association with pain [ 22 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study done on 50 participants, (25 with peripheral arterial disease (PAD) and periodontitis and 25 with periodontitis and without PAD) to examine the correlation between PAD and periodontal disease by examining the levels of inflammatory cytokines, PTX3, and high-sensitive C-reactive protein and periodontal clinical parameters, it was observed that the periodontal clinical parameters as well as the biochemical parameters were higher in the group with PAD and periodontitis. [18]…”
Section: Discussionmentioning
confidence: 99%